Estimation of the Required Bio-fuels Substituting Petroleum-based Fuels in Vehicles in the Island of Crete, Greece - Vourdoubas, John (Journal of Agricultural Studies, 2021)
The required bio-fuels for substituting petroleum-based fuels in vehicles in the island of Crete, Greece have been estimated. The quantities of gasoline and diesel oil currently used in vehicles in Crete as well as their GHG emissions have been calculated. The quantities of bio-ethanol and bio-diesel substituting 14% of them, according to the EU goal for 2030, have been evaluated. The necessary land area for cultivating energy crops producing the required bio-fuels has been also calculated. The total quantity of gasoline and diesel oil used in vehicles in 2020 in Crete has been estimated at 273,231 tons while their CO2 emissions at 886,702 tons. The bio-ethanol required for substituting 14% of the annual gasoline consumption has been calculated at 29,709 tons while the bio-diesel required for substituting 14% of the annual diesel oil consumption at 24,802 tons. The necessary land area cultivated with sugar beet producing the abovementioned quantity of bio-ethanol has been estimated at 7,427 ha while the necessary land area cultivated with rape seed producing the abovementioned quantity of bio-diesel has been estimated at 24,802 ha. The overall necessary land area, at 32,229 ha, corresponds at 3.81% of the total area in Crete. Energy crops have not been cultivated so far in Crete while the land availability is limited. It is proposed that apart from using bio-fuels in conventional vehicles equipped with ICEs different options for reducing GHG emissions in transportation, including the use of electric vehicles, should be considered in Crete.